EFEKTIVITAS MODEL INQUIRY BASED LEARNING BERBANTUAN MEDIA MILLEALAB TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Ni Kadek Wanti; I Wayan Suastra; Putu Widiarini (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Critical thinking skills are competencies that must be developed in physics education to support students’ ability to analyze, evaluate, and solve problems scientifically. However, physics education in schools is still dominated by conventional approaches, so the development of students’ critical thinking skills has not been optimal. Although the Inquiry-Based Learning (IBL) model has been widely implemented to enhance critical thinking skills, the use of the MilleaLab medium integrated with the IBL model remains limited. This study aims to describe students’ critical thinking skill profiles before and after Inquiry-Based Learning facilitated by the MilleaLab medium and to analyze differences in critical thinking skills between students who learn using this model and those in conventional learning settings. This study is a quasi-experimental study using a pretest-posttest control group design. The study population consists of all 11th-grade students at Nusa Penida State High School 1 enrolled in physics classes, comprising four classes: 11th Grade Health 1, 11th Grade Health 2, 11th Grade Health 3, and 11th Grade Business 1. The sample consists of the experimental group (11th Grade Health 2), which received Inquiry-Based Learning supported by MilleaLab media, and the control group, which received conventional instruction. Data were analyzed using descriptive and inferential analysis with the aid of Microsoft Excel 365 and SPSS Version 31. The results of the study show that the critical thinking skills of students in both groups improved after the instruction, but the improvement in the experimental group was greater than that in the control group. Furthermore, there was a difference in the critical thinking skills of students in the two groups. These findings indicate that the application of the Inquiry-Based Learning model supported by the MilleaLab media is effective in improving students’ critical thinking skills. Thus, the integration of the Inquiry-Based Learning model with the MilleaLab media serves as an innovative learning alternative to support the development of critical thinking skills in physics education. ABSTRAK Kemampuan berpikir kritis merupakan kompetensi yang harus dikembangkan dalam pembelajaran fisika untuk mendukung kemampuan siswa dalam menganalisis, mengevaluasi, dan memecahkan masalah secara ilmiah. Namun, pembelajaran fisika di sekolah masih didominasi oleh pendekatan konvensional sehingga pengembangan kemampuan berpikir kritis siswa belum optimal. Meskipun model Inquiry Based Learning (IBL) telah banyak diterapkan untuk meningkatkan kemampuan berpikir kritis, pemanfaatan media MilleaLab yang diintegrasikan dengan model IBL masih terbatas. Penelitian ini bertujuan mendeskripsikan profil kemampuan berpikir kritis siswa sebelum dan sesudah pembelajaran Inquiry Based Learning berbantuan media MilleaLab serta menganalisis perbedaan kemampuan berpikir kritis antara siswa yang belajar menggunakan model tersebut dan pembelajaran konvensional. Penelitian ini merupakan penelitian eksperimen semu (quasi experiment) dengan rancangan pretest-posttest control group design. Populasi penelitian adalah seluruh siswa kelas XI SMA Negeri 1 Nusa Penida yang mengikuti pembelajaran fisika, terdiri dari 4 kelas, yaitu kelas XI Kesehatan 1, XI Kesehatan 2, XI Kesehatan 3, dan XI Bisnis 1 , dengan sampel yang terdiri atas kelompok eksperimen (kelas XI Kesehatan 2) yang memperoleh pembelajaran Inquiry Based Learning berbantuan media MilleaLab dan kelas kontrol yang memperoleh pembelajaran konvensional. Data dianalisis menggunakan analisis deskriptif dan inferensial berbantuan Microsoft Excel 365 dan SPSS versi 31. Hasil penelitian menunjukkan bahwa kemampuan berpikir kritis siswa pada kedua kelompok mengalami peningkatan setelah pembelajaran, namun peningkatan pada kelompok eksperimen lebih tinggi dibandingkan dengan kelompok kontrol. Selain itu, terdapat perbedaan antara kemampuan berpikir kritis siswa pada kedua kelompok. Temuan ini menunjukkan bahwa penerapan model Inquiry Based Learning berbantuan media MilleaLab efektif dalam meningkatkan kemampuan berpikir kritis siswa. Dengan demikian, integrasi model Inquiry Based Learning dengan media MilleaLab menjadi alternatif pembelajaran yang inovatif untuk mendukung pengembangan kemampuan berpikir kritis dalam pembelajaran fisika.